Techno-economic analysis of biodiesel production from dairy waste scum oil (DWSO) via microwave heating transesterification - Mohd Johari, Siti Aminah; Muhammad, Ayoub; Ahmad Farid, Mohammed Abdillah; Rashidi, Nor Adilla; Agustian, Joni; Borhan, Azry; Aqsha, Aqsha; Farrukh, Sarah (Springer Science and Business Media, 2025)
Fossil fuel dependency in the transport sector presents urgent sustainability and climate concerns. Biodiesel offers a renewable alternative, especially when derived from waste-based feedstocks. This study evaluates the techno-economic feasibility of producing biodiesel from dairy waste scum oil (DWSO) via microwave-assisted transesterification, using experimentally optimized lab-scale conditions (65℃, 15 min, 3 wt. % Li-ECaO catalyst, 16:1 methanol-to-oil ratio). The process achieved a biodiesel yield of 75.4 wt. %, with 77% methanol and 95% catalyst recovery. These values were scaled to an annual production of 1.20 million kg of biodiesel and 126,540 kg of crude glycerol. Capital expenditure (CAPEX) was estimated at $3.69 million (RM 17.35 million), and annual operating expenditure (OPEX) at $0.36 million (RM 1.70 million). At a biodiesel price of $0.43/kg (RM 2.04/kg), the model yielded $0.52 million (RM 2.45 million) in annual revenue, with a net present value (NPV) of $3.58 million (RM 16.84 million), a payback period of 7.65 years, and a return on investment (ROI) of 6.47%. Sensitivity analysis was performed on five critical parameters: biodiesel price ($0.38–0.53/kg; RM 1.80–2.50/kg), methanol recovery (60–90%), catalyst reuse cycles (5–20), feedstock cost ($0.00–0.064/kg; RM 0.00–0.30/kg), and operating time (6000–8400 h/year). Variations in these inputs shifted NPV from $0.49 to $6.74 million (RM 2.30–RM 31.70 million), and the payback period (PBP) from 4.5 to 12.6 years. Enhancing methanol recovery and extending catalyst reuse increased NPV to $4.02 million (RM 18.90 million), demonstrating the system’s economic resilience and scalability for decentralized waste-to-energy applications.